Nightwood Theatre A Woman's Work Is Always Done - Shelley Scott (Canadian Plays, 2010)
Nightwood Theatre is the longest-running and most influential feminist theatre company in Canada. Since 1979, the company has produced works by Canadian women, providing new opportunities for women theatre artists. It has also been the "home company" for some of the biggest names in Canadian theatre, such as Ann-Marie MacDonald. In Nightwood Theatre, Scott describes the company's journey toward defining itself as a feminist theatre establishment, highlighting its artistic leadership based on its relevance to diverse communities of women. She also traces Nightwood's relationship with the media and places the theatre in an international context by comparing its history to that of like companies in the U.K. and the U.S.